Identification of Halloween Genes and RNA Interference-Mediated Functional Characterization of a Halloween Gene shadow in Plutella xylostella - Peng, Lu; Wang, Lei; Zou, Ming-Min; Vasseur, Liette; Chu, Li-Na; Qin, Yu-Dong; Zhai, Yi-Long; You, Min-Sheng (Frontiers in Physiology, 2019)
Ecdysteroids play an essential role in controlling insect development and reproduction. Their pathway is regulated by a group of enzymes called Halloween gene proteins. The relationship between the Halloween genes and ecdysteroid synthesis has yet to be clearly understood in diamondback moth, Plutella xylostella (L.), a worldwide Lepidoptera pest attacking cruciferous crops and wild plants. In this study, complete sequences for six Halloween genes, neverland (nvd), shroud (sro), spook (spo), phantom (phm), disembodied (dib), shadow (sad), and shade (shd), were identified. Phylogenetic analysis revealed a strong conservation in insects, including Halloween genes of P. xylostella that was clustered with all other Lepidoptera species. Three Halloween genes, dib, sad and shd were highly expressed in the adult stage, while nvd and spo were highly expressed in the egg and pupal stages, respectively. Five Halloween genes were highly expressed specifically in the prothorax, which is the major site of ecdysone production. However, shd was expressed predominantly in the fat body to convert ecdysone into 20-hydroxyecdysone. RNAi-based knockdown of sad, which is involved in the last step of ecdysone biosynthesis, significantly reduced the 20E titer and resulted in a longer developmental duration and lower pupation of fourth-instar larvae, as well as caused shorter ovarioles and fewer fully developed eggs of P. xylostella. Furthermore, after the knockdown of sad, the expression levels of Vg and VgR genes were significantly decreased by 77.1% and 53.0 %. Meanwhile, the number of eggs laid after 3 days was significantly reduced in sad knockdown females. These results suggest that Halloween genes may play a critical role in the biosynthesis of ecdysteroids and be involved in the development and reproduction of P. xylostella. Our work provides a solid basis for understanding the functional importance of these genes, which will help to screening potential genes for pest management of P. xylostella.